Chess tournament management system (scoring module) - Khor, William Kieng Ann (2005)
Chess is the game that has gained popularity among the people around the world.Nowadays, there are a lot of Chess Competition and Tournament held in all around the world. However, to organize such chess tournament,a lot time and resources is needed to perform the administrative work during the competition. One of the administrative tasks in organizing the chess tournament is to calculate the scoring and rating as well as to produce the standing table. Lots of time is spent in this work and it will place a delay on other administrative work such as pairing the player in the tournament. Instead that, when the confusion situation occurred such as the changes of previous round result, this will leads to mistake in re-calculating the score. Thus, a Chess Tournament Management System-Scoring Module is developed to deal with such situation. This system is the conversion of the rules and procedure in calculating chess score. It performs all the administrative work in handling the score for chess tournament and produce the functionalities in calculating the score (point and SolkOfi) as well as the rating. It also produces the feature such as generate the standing table, rating/ranking of player and allow the modification of the previous results without affecting the entire tournament. By developing such system to deal with chess administrative work (Score Module), it will lessen the problem during organizing the Chess Tournament.Lots of time and administrative resources can be reduced.